The impacte of the use different sources of oil on the growth performance fingerling of common carp (Cyprinus carpio L.) - Al-Faiz, Nawras A.; Saleh, Jassim H.; Al-Hason, Ahmad S. (Iraqi Journal of Aquaculture, 2022)
This study was conducted to determine the influence of oil sources on growth performance of fish common carp Cyprinus carpio. Four diets were formed which similar in their protein content and contains four different sources of oil which [Corn oil (A), palm oil (B), sunflower oil (C) and fish oil (D)] 64 fish average weight ranged between (1.598 - 1.544) g were distributed randomly on eight plastic circular form basins with capacity of 20 liters of water. Feeding fish have been tested diets on the rate of 5 % of body weight by repeating each treatment for a period of 42 days. The results showed that there is no significant difference between the treatments (p>0.05) in the values of the final weight, specific growth rate, relative growth rate and food conversion rate. As the weight increase was no significant differences (p>0.05) between treatments (A, B, C), the treatment D (fish oil) was better than treatments (B, A) with significant difference (p<0.05) and did not different.